2006
DOI: 10.1089/scd.2006.15.839
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Reflects Shared and Unique Characters for CD34+and CD133+Cells

Abstract: CD34 and CD133 are the most commonly used markers to enrich hematopoietic stem cells (HSCs). Positively selected HSCs are increasingly used for autologous and allogeneic transplantation, yet the biological properties of CD34(+) and CD133(+) cells are largely unknown. In the present study, a genome-wide gene expression analysis of human cord blood (CB)-derived CD34(+) cells was performed. The CD34(+) gene expression profile was compared to an identically constructed CD133(+) gene expression profile to reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…A recent study that evaluated the gene expression profiles of human cord blood subpopulations identified LDOC1 mRNA as up-regulated in the CD34 ϩ /CD133 ϩ subpopulation, which contains hematopoietic stem cells and progenitor cells, compared with the more mature CD34 Ϫ /CD133 Ϫ subpopulation. 25 Taken together, these findings suggest that during the course of normal B-cell development LDOC1 mRNA levels may vary with maturational stage and state of activation. An assessment of B cells obtained from different compartments and subjected to a variety of different stimuli is required to address this question.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study that evaluated the gene expression profiles of human cord blood subpopulations identified LDOC1 mRNA as up-regulated in the CD34 ϩ /CD133 ϩ subpopulation, which contains hematopoietic stem cells and progenitor cells, compared with the more mature CD34 Ϫ /CD133 Ϫ subpopulation. 25 Taken together, these findings suggest that during the course of normal B-cell development LDOC1 mRNA levels may vary with maturational stage and state of activation. An assessment of B cells obtained from different compartments and subjected to a variety of different stimuli is required to address this question.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, CD133 + cells in the hematopoietic system appear to be ancestral to CD34 + cells, especially as the latter can be generated in vitro from CD133 + CD34 − cells [66] . Furthermore, CD133 + cells from cord blood display a higher proliferative activity [66,67] and a more primitive gene expression profile [68] than CD34 + cells. Thus far, the phenotype of CD34-negative HSCs has been characterized by the concurrent absence of CD38, lack of lineage-specific cell surface antigens, as well as by expression of CD133 [69] .…”
Section: Phenotype and Isolation Of Human Hematopoietic Stem Cellsmentioning
confidence: 97%
“…A comparative determination of the reactivity to mAb against CD133 and the ability to exclude Rho123 was performed to see whether these markers correlate with specific CD34 epitope patterns or with each other. By using transcriptional profiling analysis [35], (global) gene expression [36][37][38] and functional analysis [16,39,40], many authors have reported that CD133+ cells reflect a more primitive stage of HPC. This was characterised by a high content of scid-re-populating and long-term culture-initiating cells [15].…”
Section: Discussionmentioning
confidence: 99%